Hot wages: How do heat waves change the earnings distribution? - Giulia Valenti; Francesco Vona (Fondazione Eni Enrico Mattei (FEEM), 2024)
This paper examines the impact of temperature shocks, measured by cold and heat waves, on labour market outcomes across 14 European countries. Using retrospective individual-level data from the Survey on Health, Ageing, and Retirement in Europe (SHARE) and daily climate data from the E-OBS dataset, we analyze the effect on wages and occupational transition. By leveraging plausibly exogenous weather shocks, we find that heat waves significantly reduce individual income, with losses accumulating over time. Moreover, our analysis documents that older individuals, those with severe health conditions, and workers in heat-exposed occupations experience particularly large income reductions. Losses are also more pronounced in Mediterranean and Eastern European countries, as well as in regions with less regulated wage-setting mechanisms. Additionally, our findings suggest that heat waves increase the likelihood of changing jobs and in particular to transition from heat-exposed to non-heat-exposed occupations. These results underscore the need for targeted policy interventions to mitigate economic losses and protect vulnerable workers in the face of increasing climate variability.
Keywords: Q54; J24; J30; 330; Temperature; labour market; wages; occupational transition